2020
DOI: 10.4236/ojneph.2020.104026
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Primary Focal Segmental Glomerulosclerosis (FSGS) in Adults Treated in a Dakar Single Center: About 58 Cases

Abstract: Introduction: The evolution of primary FSGS is often marked by the occurrence of relapse and corticosteroid resistance and the therapeutic options are numerous and have limited effectiveness. The objective of our study was to assess our practice in this lesion. Patients and Methods: We carried out a retrospective study of patients treated for primary FSGS the period January 1, 2010 to September 30, 2018. The clinical pathological, therapeutic and evolutive characteristics were studied. Results: Fifty-eight pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…The age at diagnosis ranged from 20 to 87 years. Consistent with the findings of previous studies, the current study found significant male dominance 11,[18][19][20] . One retrospective study by Stirling et al, using patient data from five different UK centers, showed that the mean age was similar to that in our study 20 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The age at diagnosis ranged from 20 to 87 years. Consistent with the findings of previous studies, the current study found significant male dominance 11,[18][19][20] . One retrospective study by Stirling et al, using patient data from five different UK centers, showed that the mean age was similar to that in our study 20 .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the mean proteinuria level was found to be in the nephrotic range, at 8.5±4.0 g/day. The rates of hypertension (37%) 12,18 and microscopic hematuria (40.7%) 12 were similar to those in previous studies. In According to the Kidney Disease Improving Global Outcomes (KDIGO) recommendations, patients with MCD and primary FSGS can be treated with corticosteroids daily or every other day, and if there are no contraindications, corticosteroids are recommended as first-line therapy 7,23 .…”
Section: Discussionsupporting
confidence: 88%